Tratamiento contable del activo biológico tilapia bajo NIC 41. - Peralta Neira, Maritsa Gabriela (My University, 2022)
In this work of a complex nature, the costs that arise from the production process of the biological active tilapia are estimated, the same that has a duration of 6 months for its development propitiated from the sowing. In this sense, the initial investment, elements of the cost by processes and its measurement and valuation under international accounting standard 41 were taken into account. For its analysis and development, the processes derived from aquaculture production were determined, their stages and their application described from the documentary observation of scientific articles, books and regulations applicable to the subject; in addition to the chair of agricultural accounting. Among the main findings are evidenced the stages ranging from the preparation of swimming pools, planting, growth, fattening and harvesting of tilapia; for all this, economic resources intervene and that when grouped together generate costs in the processes, generating through each one monetary needs used in the different factors of production determinants of the cost of production such as raw material, labor and indirect costs of production.
En este trabajo de carácter complexivo se estiman los costos que se desprenden del proceso productivo del activo biológico tilapia, el mismo que tiene una duración de 6 meses para su desarrollo propició a partir de la siembra. En este sentido se tomó en cuenta la inversión inicial, elementos del costo por procesos y su medición y valoración bajo la Norma Internacional de Contabilidad 41. Para su análisis y desarrollo se determinaron los procesos derivados de la producción acuícola, sus etapas y su aplicación descritos desde la observación documental de artículos científicos, libros y normativas aplicables a la temática; además de la cátedra de contabilidad agropecuaria. Entre los principales hallazgos se evidencian las etapas que van desde la preparación de piscinas, la siembra, crecimiento, engorde y cosecha de la tilapia; para todo ello intervienen recursos económicos y que al agruparlos generan costos en los procesos, generando a través de cada uno necesidades monetarias empleados en los diferentes factores de producción determinantes del costo de producción como la materia prima, mano de obra y costos indirectos de producción.
Keywords: ACTIVO BIOLÓGICO; NIC 41; COSTOS; VALOR RAZONABLE